Effects of rootstock genotypes on compatibility, biomass, and the yield of Welschriesling - S. Vršič; B. Pulko; L. Kocsis (Horticultural Science, 2016)
The aim of this work is to determine the compatibility, the scion biomass, and the yield of the grapevine variety Welschriesling grafted onto 12 grapevine rootstocks. As an index of compatibility, the callus development and graft success were determined. Dry weight of canes was measured at the end of the growing seasons (2011-2014), while root dry weight only in the first year in the nursery. The grape yield was measured in the first production year. Welschriesling showed good compatibility with all examined rootstocks. More than 85% of grafts had a complete callus development (8BČ rootstock 100%). The average of graft success in the nursery was 67%, but the average of 5BB, G251, and G103 was above 80%. The G103 rootstock had the highest root dry weight after one season. The dry weight of canes in vineyards was above the average with 5BB, SO4, Binova, Börner, and M V rootstocks. All Georgikon rootstocks had a lower cane dry weight per vine than the others. The highest yields were recorded on SO4, G251, and Börner rootstocks.